Sexual dysfunction among post partum women and its associated risk factors in primary care clinics in Kuantan, Pahang - a preliminary report - Jamani, Nurjasmine Aida; Khalid, Nur Nadrah; Abd. Aziz, Karimah Hanim; Draman, Nani (Academy of Family Physicians of Malaysia, 2018)
Childbirth is one of the recognized risk factor for female sexual dysfunction (FSD). Despite high prevalence of female sexual dysfunction worldwide, there is very limited data concerning sexual dysfunction in postpartum women. The aim of our study is to determine the prevalence of FSD and its subtypes among postpartum women in primary health clinics in Kuantan, Pahang.